The Structures of Trump’s Political Discourse - Anggraini, Rini; Sawirman, Sawirman; Marnita, Rina (Center of Language and Cultural Studies [CLCS], 2021)
This study explains the discourse structure of antagonism in one of Trump’s political speeches. The analysis also describes the function of antagonistic discourse for Trump’s political purposes against his opponents from the Democratic Party like Joe Biden and Elizabeth Warren. CDA is the approach used in this research. The theories of political frontier antagonism from Malmberg, Howarth, and Stravakakis supported by the annihilating dynamics of meaning from O’Dawyer are applied to the data taken from the transcription of Trump’s political speeches. The findings show that Trump utilizes specific nouns modified by adjectives to form a political barrier of antagonism between him against the opponents of the Democratic Party. The structure of discourse found in this study shows that Trump uses antagonism in his political speech to inflict a heavy blow to his opponents’ political image.